COVID-19 pandemic, mechanical reperfusion and 30-day mortality in ST elevation myocardial infarction. Issue 6 (28th October 2021) - De Luca, Giuseppe; Algowhary, Magdy; Uguz, Berat; Oliveira, Dinaldo C; Ganyukov, Vladimir; Zimbakov, Zan; Cercek, Miha; Jensen, Lisette Okkels; Loh, Poay Huan; Calmac, Lucian; Roura-Ferrer, Gerard; Quadros, Alexandre; et al.
Abstract : Objective: The initial data of the International Study on Acute Coronary Syndromes - ST Elevation Myocardial Infarction COVID-19 showed in Europe a remarkable reduction in primary percutaneous coronary intervention procedures and higher in-hospital mortality during the initial phase of the pandemic as compared with the prepandemic period. The aim of the current study was to provide the final results of the registry, subsequently extended outside Europe with a larger inclusion period (up to June 2020) and longer follow-up (up to 30 days). Methods: This is a retrospective multicentre registry in 109 high-volume primary percutaneous coronary intervention (PPCI) centres from Europe, Latin America, South-East Asia and North Africa, enrolling 16 674 patients with ST segment elevation myocardial infarction (STEMI) undergoing PPPCI in March/June 2019 and 2020. The main study outcomes were the incidence of PPCI, delayed treatment (ischaemia time >12 hours and door-to-balloon >30 min), in-hospital and 30-day mortality. Results: In 2020, during the pandemic, there was a significant reduction in PPCI as compared with 2019 (incidence rate ratio 0.843, 95% CI 0.825 to 0.861, p<0.0001). This reduction was significantly associated with age, being higher in older adults (>75 years) (p=0.015), and was not related to the peak of cases or deaths due to COVID-19. The heterogeneity among centres was high (p<0.001). Furthermore, the pandemic was associated with a significant increase in door-to-balloon time (40 (25–70) min vs 40 (25–64) min, p=0.01) and total ischaemia time (225 (135–410) min vs 196 (120–355) min, p<0.001), which may have contributed to the higher in-hospital (6.5% vs 5.3%, p<0.001) and 30-day (8% vs 6.5%, p=0.001) mortality observed during the pandemic. Conclusion: Percutaneous revascularisation for STEMI was significantly affected by the COVID-19 pandemic, with a 16% reduction in PPCI procedures, especially among older patients (about 20%), and longer delays to treatment, which may have contributed to the increased in-hospital and 30-day mortality during the pandemic. Trial registration number: NCT04412655 .